2016
DOI: 10.1111/jonm.12386
|View full text |Cite
|
Sign up to set email alerts
|

The factors influencing burnout and job satisfaction among critical care nurses: a study of Saudi critical care nurses

Abstract: These results provide clear evidence of the need for nurse managers and policy makers to devise strategies to help nurses better cope with a stressful work environment, thereby also improving job satisfaction among Saudi national critical care nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 35 publications
4
57
1
8
Order By: Relevance
“…Evidence has shown that higher burnout levels among nurses caused by work stress are associated with lower job satisfaction [10]. Burnout is a predictor of job satisfaction [11]. Moreover, highly satisfied and free from burnout nurses ish and Polish health care systems are mainly provided by the public sector.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that higher burnout levels among nurses caused by work stress are associated with lower job satisfaction [10]. Burnout is a predictor of job satisfaction [11]. Moreover, highly satisfied and free from burnout nurses ish and Polish health care systems are mainly provided by the public sector.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study of Alostaz regarding satisfaction of nurses in Saudi Arabia might be biased by the small sample size (only 60 participants) [15]. The more recent study by Alharbi et al from that country presented only a moderate satisfaction level of critical care nurses [18]. According to these data, we could not find any scheme or correlation to understand job satisfaction of nurses in different countries.…”
Section: Discussionmentioning
confidence: 71%
“…The multidimensional approach often used in job satisfaction research has resulted in researchers investigating a whole host of intrinsic, personal factors, and extrinsic, organizational factors (Khalaf et al 2019). Previous research in Saudi nurses indicates that a range of personal and organizational factors correlate with job dissatisfaction including low pay, high turnover rate, stress, burnout and workload (Al-Dossary et al 2012;Alharbi et al 2016), whilst religion and culture support job satisfaction (Alotaibi et al 2016). Indeed, understanding Islamic values and cultural traditions are important components of effective care when nursing Muslim patients (Albaqawi et al 2019;Al-Yateem et al 2015;Atkinson 2015).…”
Section: Discussionmentioning
confidence: 99%